Assessing usefulness and researcher satisfaction with consent form templates - Larson, Elaine L. (J Clin Transl Sci, 2017)
INTRODUCTION: We aimed to improve the research consenting process by developing and evaluating simplified consent forms. METHODS: Four templates written at the eighth-tenth grade reading level were developed and trialed by a group of experts in clinical research, health literacy, national regulatory requirements, and end users. Researchers from protocols which had received expedited review were surveyed at 2 time points regarding their use and assessment of the templates. RESULTS: At baseline 18/86 (20.9%) responding researchers had heard of the templates and 5 (5.8%) reported that they had used them; 2 years later, 54.2% (32/59) had heard of the templates and 87.5% (28/32) had used them (p<0.001). CONCLUSIONS: Consent form templates may be one mechanism to improve patient comprehension of research protocols as well as efficiency of the review process, but require considerable time for development and implementation, and one key to their success is involvement and support from the IRB and technical staff.